The law of Indecent Law and criminal justice system - Mohamad Yunus, Mohamad Ismail (Sweet & Maxwell Asia, 2016)
Is it legally correct to say that indecent assault means an assault, which has in it an element of indecency? According to Ralph Gibson LJ in the celebrated case of R v Court (1987) 84 Cr App R 210, CA, indecent assault means an assault accompanied by circumstances of indecency on the part of the defendant towards the complainant, and “indecent” has been defined as overtly sexual. What has the prosecution got to prove to establish the defendant’s guilt on this charge of indecent assault? It is said that they must prove two things. Firstly, that the defendant’s conduct was such that it would appear to an ordinary observer as an affront to modesty: conduct, which contravenes right-thinking people’s ideas of standards of decent behaviour. Secondly, that the defendant had an indecent intention in doing what he did. So, first indecent assault must represent conduct that would appear to the ordinary observer as an affront to modesty and secondly it must have an indecent intention (motive) on the part of the defendant in doing what he did. However, in Malaysia, under section 354 of the Malaysian Penal Code, the term “assault or use of criminal force to a person with intent to outrage modesty” is used instead of “indecent assault”. The question is, do the above legal requirements, which were laid down in R v Court, need to be fulfilled as the essential ingredients under section 354 of the Malaysian Penal Code?